Analisis Rasio Profitabilitas dan Solvabilitas PT Sri Rejeki Isman Tbk (Sritex) dan Pesaingnya di Industri Tekstil - Adila Durrotul Ghina; Heru Pribowo; Dzahin Syauqi Muhammad (RJABM (Research Journal of Accounting and Business Management), 2026)
This study aims to analyze the financial performance of PT Sri Rejeki Isman Tbk by using profitability and solvency ratios. The results of the ratio analysis will be compared with other competitors in the textile industry. The research method employed is a descriptive research method. The data used consist of financial statements for the period of 2020 to the third quarter of 2024. The data are limited to the third quarter of 2024 because the company went bankrupt in 2024. The results of the study indicate that the company’s financial performance was poor in terms of its ability to generate profits and manage its debts. Competing companies demonstrated significantly better performance in generating profits and managing debts.